Analysis of ring sourced diffraction with rigid and impedance boundary condition - (:unkn) unknown (Politechnica University of Bucharest, 2019)
The diffraction of sound waves emanating from a ring source is investigated rigorously by using the Wiener-Hopf technique. Two different geometry is considered which are semi-lined and full-lined with different linings. An exact solution is obtained based on the boundary condition. At the end of the analysis, the influence of the problem parameters and comparison of geometries are presented graphically. © 2019, Politechnica University of Bucharest. All rights reserved.
Keywords: Diffraction; Duct; Fourier transform; Wiener-Hopf